The way to happiness [ a common sense guide to better living - Hubbard, L. Ron [ (La Fayette Ron)] , 1911-1986 (L. Ron Hubbard Library, 2009)
"In a chaotic world of plummeting moral standards, The Way to Happiness: a common sense guide to better living reaches out to millions of people across 130 nations with a message of integrity, morality and trust. Now The Way to Happiness has been produced as a powerful feature-length film. And with that adaptation comes a cinematic experience unlike any you have ever seen. For here, running parallel with the full text narration of the book, you will find a series of interwoven stories, each featuring different individuals caught up in the drive and drama of living. You'll follow their losses, wrong turns, dilemmas, trauma and triumphs - until each person finally arrives onto the way to happiness. Here is a film about life, finding one's way and the persistence of the human spirit. And in the end, you experience a riveting visual presentation of The Way to Happiness's universal and timeless message - at once compelling and inspiring, a message you can now pass on to others and so enhance their survival and future as well." from back cover